Measuring Protein Aggregation and Stability Using High-Throughput Biophysical Approaches - Kwan, Tristan O. C.; Kolek, Stefan A.; Danson, Amy E.; Reis, Rosana I.; Camacho, Ines S.; Shaw Stewart, Patrick D.; Moraes, Isabel (Frontiers in Molecular Biosciences, 2022)
Structure-function relationships of biological macromolecules, in particular proteins, provide crucial insights for fundamental biochemistry, medical research and early drug discovery. However, production of recombinant proteins, either for structure determination, functional studies, or to be used as biopharmaceutical products, is often hampered by their instability and propensity to aggregate in solution in vitro. Protein samples of poor quality are often associated with reduced reproducibility as well as high research and production expenses. Several biophysical methods are available for measuring protein aggregation and stability. Yet, discovering and developing means to improve protein behaviour and structure-function integrity remains a demanding task. Here, we discuss workflows that are made possible by adapting established biophysical methods to high-throughput screening approaches. Rapid identification and optimisation of conditions that promote protein stability and reduce aggregation will support researchers and industry to maximise sample quality, stability and reproducibility, thereby reducing research and development time and costs.